2014
DOI: 10.1039/c3em00591g
|View full text |Cite
|
Sign up to set email alerts
|

Photo-reactivity of natural dissolved organic matter from fresh to marine waters in the Florida Everglades, USA

Abstract: Natural dissolved organic matter (DOM) is the major absorber of sunlight in most natural waters and a critical component of carbon cycling in aquatic systems. The combined effect of light absorbance properties and related photo-production of reactive species are essential in determining the reactivity of DOM. Optical properties and in particular excitation-emission matrix fluorescence spectroscopy combined with parallel factor analysis (EEM-PARAFAC) have been used increasingly to track sources and fate of DOM.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 78 publications
9
50
0
Order By: Relevance
“…This has been observed in natural systems as a previous study of DOM photochemistry identified divergent trends in 1 O 2 and 3 DOM production as DOM moved through an estuary. 90 Our observation that 3 DOM formation rates are constant with molecular weight suggests that environmental or engineered processes that modify molecular weight may not alter the carbon-normalized 3 DOM formation rates. However, the decrease in light absorbance that accompanies decreasing DOM molecular weight may allow indirect photodegradation to occur deeper in the water column and increase the overall contaminant loss rate.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…This has been observed in natural systems as a previous study of DOM photochemistry identified divergent trends in 1 O 2 and 3 DOM production as DOM moved through an estuary. 90 Our observation that 3 DOM formation rates are constant with molecular weight suggests that environmental or engineered processes that modify molecular weight may not alter the carbon-normalized 3 DOM formation rates. However, the decrease in light absorbance that accompanies decreasing DOM molecular weight may allow indirect photodegradation to occur deeper in the water column and increase the overall contaminant loss rate.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…However, at high concentration of SRNOM and in salt waters indirect photolysis can have a significant effect on chlorpyrifos degradation. The importance of the amount and the type of dissolved organic matter (DOM) on the steady-state concentration of intermediate radicals was reported by Timko et al [40]. The authors found out that that the formation rates of singlet oxygen ( 1 O 2 ) radical, hydroxyl radicals ( OH) and carbonate radical and their steady state concentration decreased along the estuarine salinity gradient as a consequence of a decrease of terrestrial humic-like DOM.…”
Section: Photolysis Kineticsmentioning
confidence: 85%
“…Moreover, studies in fresh-water and estuarine water showed that estuarine samples are more photo-reactive and have higher RS formation rates along with higher organic carbon content than fresh-water samples Housari et al, 2010). Another finding demonstrated that increasing humic concentration could also enhance •OH photoproduction rates (Mopper et al, 1990) and the main source of ¹O₂ are the moieties that are present in the terrestrial humic substances (Timko et al, 2014). Alternatively, halide radicals such as bromide or chloride could contribute to the photoproduction of RS from DOM as well .…”
Section: Dissolved Organic Matter Is Known As a Photosensitizer And Imentioning
confidence: 89%
“…Thus, TS7 November sample showed a low a₂₅₅ and DOC value which is similar to FB samples. On the basis of previous reports, the DOC concentration in the SRS decreased from the upstream to downstream while the TS showed an opposite trend Timko et al, 2014;Romera-Castillo et al, 2015). Peat based fresh-water marsh sub-environment (SRS2) showed a significantly higher concentration of DOC (Avg.…”
Section: Cluster Analysismentioning
confidence: 99%
See 1 more Smart Citation